A-priori assessment of subgrid scale models for large-eddy simulation of multiphase primary breakup. (30th March 2018) - Ketterl, S.; Klein, M.
Highlights: Extensive comparison of published LES models for the unclosed terms emerging in the context of two phase flows. A-priori model analysis dependent on the location relative to the interface. Derivation of two new models, one for scalar flux and one for subgrid stresses. Both models predict the SGS terms with comparable or better accuracy than the alternative closures. Abstract: While Large-Eddy Simulation (LES) of single phase flows is well established in computational fluid dynamics, LES of multiphase flow is at an early development stage. The presence of the phase interface causes additional subgrid scale (SGS) terms to appear in the LES formalism. Not only turbulent structures but also interfacial deformations need to be captured by SGS models. The fidelity of multiphase LES depends on the complex interaction between turbulence and the phase interface at the unresolved scale. A variety of traditional and more recent SGS models of eddy viscosity or scale similarity type is suggested for the SGS terms in multiphase LES. Two new models for the SGS stress and for the SGS scalar flux are proposed. The first is based on a Taylor series expansion of the convolution filter, the latter is inspired by flamelet theory of turbulent premixed combustion. The closure models are a-priori assessed with respect to explicitly filtered direct numerical simulation (DNS) data of primary breakup of a liquid jet. The model performance is evaluated based on a correlation analysis and an order of magnitude study. Model accuracy is discussed depending on the filter size and the flow region. Promising candidates for a-posteriori analysis are identified.